2020
DOI: 10.3390/jfmk5030057
|View full text |Cite
|
Sign up to set email alerts
|

Is Supine Position Superior to Prone Position in the Surgical Pinning of Supracondylar Humerus Fracture in Children?

Abstract: Background: Supracondylar humerus fracture (SCHF) is a frequent injury in pediatric ages. Closed reduction and percutaneous pin fixation is a common treatment of displaced SCHF. Surgery is usually performed in the supine position; otherwise the prone position allows an easier fracture reduction and a safe placement of pins. The aim of study is to compare the clinical and radiographic results of the treatment of displaced SCHF, comparing two different intra-operative positionings. Methods: 59 SCHF affected chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 37 publications
(50 reference statements)
1
15
0
Order By: Relevance
“…We observed a mean time from admission to surgery of 6.5 h which is similar to the time interval proposed by Pavone et al (<8 h) [25]. However, Schmid et al showed that postponing surgery does not influence the rate of open reductions, incidence of postoperative complications, and overall outcome [26].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We observed a mean time from admission to surgery of 6.5 h which is similar to the time interval proposed by Pavone et al (<8 h) [25]. However, Schmid et al showed that postponing surgery does not influence the rate of open reductions, incidence of postoperative complications, and overall outcome [26].…”
Section: Discussionsupporting
confidence: 87%
“…We performed closed reduction and percutaneous lateral pin fixation in the supine position of the patient. Pavone et al demonstrated good radiographic outcomes and similar complication rates after closed reduction and percutaneous pinning in Gartland type III fractures treated in either the supine or prone position of the patient [25].…”
Section: Discussionmentioning
confidence: 92%
“…Surgical technique has several constantly developing features, including patient decubitus position (lateral, supine, prone), number of portals (four principals and some accessories portals), procedure stages (anterior or posterior compartment first), and device features. From the analysis of the available literature, it is not possible to identify a gold standard [ 3 , 8 , 23 , 37 ]. We believe that, given the difficulty and the experience required to perform these procedures, surgeons who perform a pediatric elbow arthroscopy should choose the surgical technique in which they are most experienced, to minimize the risks.…”
Section: Discussionmentioning
confidence: 99%
“…SCHF should be considered any injury even with a low energy mechanism, and lateral and oblique series X-rays are the cornerstone in the diagnosis of pediatric fractures. Diagnosis at the hospital was based on clinical examination and X-rays [38]. The study describes many methods of positioning the pinning fixation for the treatment of SCHF.…”
Section: Discussionmentioning
confidence: 99%